The Economic Life Cycle and Support Systems in Asia - Sang-Hyop Lee; Andrew Mason (Asian Development Bank (ADB), 2011)
We describe the complex support systems in Asia and highlight their importance for economic growth and fiscal sustainability. Familial transfers for old age support are significant in many Asian economies, though their extent varies quite widely, and public transfer systems are less significant. This is important because the region has the opportunity to develop sustainable systems less encumbered by obligations made to current and future generations of elderly. Relying on accumulated assets rather than transfers will help the region to create capital- intensive economies that can maintain standards of living.
hdl:11540/2001
Keywords: 330; Lebenszyklus; Altersvorsorge; Intergenerationale Übertragung; Asien